ENHANCE OF SECURE HEALTH WORKER IN HOSPITAL - Sastra Wirawan; Redyanto Sidi; Muhammad Arif Sahlepi (SEAN Institute, 2023)
Indonesia is an increasingly developing country of law and the advancement of human development should also be followed by the development of the rule of law. However, the reality is that the law has always lagged behind the progress of human development. Even the development of regulations in the field of health law in the country is still far from meeting expectations, especially regarding legal protection for medical workers (doctors and nurses) when they fight to save human lives, it still often happens that they become victims as a result of the profession they are engaged in. This research is a normative research that uses selkundelr data, namely library data and legislation.